Musyawarah dan Mufakat Sebagai Solusi Pemanfaatan Tanah Fasilitas Umum Masyarakat - Eskanugraha, Andika Putra (PUSKAPSI Law Review, 2021)
Utilization of land for public facilities is the ideals of the constitution as stated that "to be used for the greatest prosperity of the people" and "land to function socially" based on Law No. 5/1960 concerning Basic Agrarian Regulations. The use of land for the public facilities does not give priority rights to a party or individual. Collective use within the community must be addressed wisely and proportionally in its use. A public road that is regarded as a public facility, no one can claim to be entitled to a road because it borders or is close to the land or occupancy. With the closed access to the use and benefitting of roads as the public facilities, it is difficult to determine the violation of the law committed. There is a Provincial Regulation which regulates the prohibition of parking on the roads, but this prohibition is not well-regulated in other regions with its legal products. Disregarding in the community to the road users as public facilities, can become a social problem and must be resolved with a consensus reflecting the Pancasila as the life point of view. Deliberation and consensus is a solution to solving problems by involving Village Traditional Institutions or similar names based on regionalism. Deliberation and consensus as a solution to the use of land for public facilities, can produce decisions in village deliberations. The Village Customary Institution as a partner to the Village Government can propose the joint use of community public facilities to be regulated in a Village Regulation. Normative legal research is the method used in this study. There is no violation of legal rules in the unwise use of public facilities, making this community problem must be resolved by the community itself by prioritizing the value of the Pancasila and after that it can be elaborated in the simplest rules in the Village Regulation.